2019
DOI: 10.1111/petr.13550
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length regulators are activated in young men after pediatric kidney transplantation compared to healthy controls and survivors of childhood cancer—A cross‐sectional study

Abstract: Chronic diseases are known to cause premature aging and frailty. Data about telomere length and telomere length‐regulating proteins after pediatric KTx are scarce. Leukocyte telomere length and gene expression level of eight telomere‐binding proteins were analyzed in 20 KTx recipients, eight childhood NBL survivors, and nine healthy controls. The influence of key clinical parameters on telomere length and on regulators of telomere length was evaluated. The telomere length in the KTx recipients tended to be sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is noteworthy that, as previously demonstrated, after kidney transplants, pediatric cancer patients exhibited a shorter blood cell telomere length compared to the controls, but presented with elevated gene expression levels of telomere length-preserving proteins ( 85 ). Therefore, also in renal cancer, a significant association between the variation of telomere length and cancer risk has been established.…”
Section: Urinary/renal Systemmentioning
confidence: 79%
“…It is noteworthy that, as previously demonstrated, after kidney transplants, pediatric cancer patients exhibited a shorter blood cell telomere length compared to the controls, but presented with elevated gene expression levels of telomere length-preserving proteins ( 85 ). Therefore, also in renal cancer, a significant association between the variation of telomere length and cancer risk has been established.…”
Section: Urinary/renal Systemmentioning
confidence: 79%
“…This study also suggests that such genotypic analyses, targeting alterations typical of the accelerated aging process, may better tailor or personalize post‐transplant management leading to optimal post‐transplant outcomes. Another very recent interesting paper focused on pediatric renal transplant recipients that suggest activation of mechanisms preserving telomere length and telomerase activity regulating factors on the quality of allografts among young recipients appears to be in line with this direction .…”
Section: Accelerated Aging: Underlying Mechanisms Impacting Transplanmentioning
confidence: 98%
“…They also play a significant role in osteoporosis, which can result in bone disease after transplantation. Calcineurin inhibitors are nephrotoxic and reduce the activity of telomere-binding proteins, thus accelerating telomere length shortening and cell senescence [89] . In other respects, it has been reported that antibiotics and immunosuppressants can change the composition of the intestinal floras, thereby destroying the homeostasis of the intestinal system [90] .…”
Section: Possible Pathogenesis Of Frailty In Kt Candidates and Recipi...mentioning
confidence: 99%
“…Calcineurin inhibitors are nephrotoxic and reduce the activity of telomere-binding proteins, thus accelerating telomere length shortening and cell senescence. [ 89 ] In other respects, it has been reported that antibiotics and immunosuppressants can change the composition of the intestinal floras, thereby destroying the homeostasis of the intestinal system. [ 90 ] Once graft loss occurs, KT recipients will re-enter the ESRD stage and will require immunosuppressive therapy.…”
Section: Possible Pathogenesis Of Frailty In Kt Candidates and Recipi...mentioning
confidence: 99%